Patent regimes and the commodification of knowledge - Benjamin Coriat; Olivier Weinstein (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
This paper analyses the evolution of the intellectual property regime (IPR), and more precisely the patent regime, in the USA since the 19th century. To do so, we consider intellectual property laws within the context of wider changes in capitalism, focusing on two main historical phases: firstly, the period covering the formation and development of 'corporate capitalism' dominated by large corporations and then the new phase, which opened up in the 1980s, marked by the rise to power of finance. From a perspective of institutional complementarities, we seek to show how the characteristics and implications of patent regimes can only be understood in relation to changes in the main institutional forms of capitalism: forms of the firm, the status of labour (the 'wage-labour nexus') and market forms.
Keywords: O34; P1; 330; firms; financialization; institutional complementarities; knowledge based economy; labor law; property rights